Chilean muralist and set designer Alejandro "Mono" González at the Filuni in Mexico: “The mural encouraged resistance against Pinochet’s dictatorship”: Mono González (REVISTA NODO, 2025)
Review of “Mono” González’s participation in Filuni Mexico.
Keywords: Wall Art; Graphic Design; Chile